Cara pemakaian mesin cara dan perawatan Mesin Pengupas Gabah Padi kepada Masyarakat Desa Amborgan Kecamatan Porsea Kabupaten Tobasa - Richard A.M Napitupulu; Perangin angin, siwan (Jurnal Visi Pengabdian Kepada Masyarakat, 2024)
Abstract Rice is an agricultural product that is the main consumption of the Indonesian people, especially the people of the province of North Sumatra and especially in the TOBASA area and the Amborgan Village Community, Porsea District. In an area there is usually only one unit of rice hulling machine. For the rice hulling process, most farmers do the milling at that place and often have to queue because of the many farmers who will hull the rice. Therefore, with the help of a rice hulling machine, it can make it easier for the community, especially the home industry, to speed up the rice hulling process. Therefore, the Mechanical Engineering Study Program, HKBP Nommensen University, carried out community service to the village of Amborgan Village, Porsea District, TOBASA Regency by donating and providing training on operating a rice hulling machine. The result is that the community and the district government, especially the TOBASA Regency DPRD, are very happy with this program. And the community there is helped by the tools donated by the UHN Mechanical Engineering Study Program because they can helpis the essence of all parts of a complete paper that contains 75-200 with 10pt font size and protrudes 1cm from the left margin and right margin. The abstract is written in less than half a page. Abstract written in English and Indonesian.